Pemanfaatan Aplikasi Pembelajaran Bahasa Arab: Mengubah Cara Belajar di Era Digital - Firdaus, Ferry Maulana; Aziz, Muhammad Tareh (Journal of Practice Learning and Educational Development, 2024)
The use of Arabic language learning applications in the digital age has brought a significant change in the way the language is learned. The Arabic language plays an important role in diplomacy, economics, international relations, and religion, making it crucial to master. Digital technology, through applications like Duolingo, Rosetta Stone, and Memrise, offers flexible and interactive solutions that enable students to learn anytime and anywhere. The research uses qualitative descriptive approaches to explore the impact of such applications on learning processes. Research results show that this application improves student motivation and involvement compared to conventional methods. Students appreciate application flexibility and interactivity, while teachers report efficiency in material preparation and improved learning outcomes. Despite the huge benefits, challenges such as technical constraints and adaptation to new technologies remain. Therefore, there is a need for continuous improvement in the application and support of educational institutions for effective integration. Overall, Arabic learning applications are an innovative and effective tool in improving Arabic language competence in the digital age.